(untitled) - Li, Charlene (Boston, 2008)
Corporate executives struggle to harness the power of social technologies. Twitter, Facebook, blogs, YouTube are where customers discuss products and companies, write their own news, and find their own deals but how do you integrate these activities into your broader marketing efforts? It's an unstoppable groundswell that affects every industry -- yet it's still utterly foreign to most companies running things now. When consumers you've never met are rating your company's products in public forums with which you have no experience or influence, your company is vulnerable. In Groundswell, Josh Bernoff and Charlene Li explain how to turn this threat into an opportunity. In this updated and expanded edition of Groundswell, featuring an all new introduction and chapters on Twitter and social media integration, you'll learn to: · Evaluate new social technologies as they emerge · Determine how different groups of consumers are participating in social technology arenas · Apply a four-step process for formulating your future strategy.
Keywords: Mạng xã hội trực tuyến,Xã hội thông tin,Online social networks,Information society; Khía cạnh kinh tế,Khía cạnh kinh tế,Economic aspects,Economic aspects